Sunrise Hope - Morgan-Cole, Trudy J.; Nang Chan Yeema (Hagerstown, Maryland, United States Review and Herald Publishing Association, 2011)
Just when she felt like giving up, Stephanie realized God was still working on all of them - and she sensed hope rising once again.
Keywords: Adult Fiction